Antimycotic Activity of Leaf Extracts of Medicinal Plants Against Dermatophytes - Jangid Renu; begum Tahira (Journal of Fungal Diversity, 2020)
Plant products have been used as medicines against fungal infectious diseases. In this research antimycotic activity of the leaf extracts of five medicinal plants (Nerium indicum, Catheranthus roseus, Lantana camera, Ziziphus mauritiana) were tested against three dermatophytes (Trichophyton mentagrophytes, Trichophyton rubrum and Microsporum. gypseum). Development of more effective and less toxic antimycotic agents is required for the treatment of dermatophytosis. The plant materials were extracted with methanol, ethanol and diethyl ether solvent to investigate their antimycotic activities in Vitro. Ethanol and methanol extracts of all selected medicinal plants were showed the positive activity against all tested dermatophytes. Diethyl ether extract was showed lowest activity against T. mentagrophytes and T. rubrum and showed moderate activity against M. gypseum. The three dermatophytes differed with regard to their susceptibility to plant extracts.
Keywords: Medicinal plants